Rethinking American grand strategy - Borgwardt, Elizabeth 1964-; Nichols, Christopher McKnight; Preston, Andrew 1973- (Oxford University Press, 2021)
This edited volume, brings together a group of preeminent scholars, many of the best and most well-regarded thinkers in the field today, to construct a historically rich account of how Grand Strategy has developed and operated in American history.
Includes index.
Keywords: Geschichte; National security / United States / History; Strategy / History; Internationales politisches System; Sicherheitspolitik; Weltordnung; Außenpolitik; United States / Foreign relations; United States / Military policy; USA; Aufsatzsammlung